Gravitating towards emission reduction targets in the G7 and E7 economies : the financial development and sustainable energy perspectives - Gyamfi, Bright Akwasi; Agozie, Divine Q.; Bekun, Festus Victor; Onifade, Stephen Taiwo (Taylor & Francis, 2024)
Governments throughout the globe are confronted with climate change issues. In the wake of the climate change conference COP26—the Glasgow consensus, the criticality of attaining emission reduction targets to restrain global average temperature to 1.5 degrees has been reemphasized. Hence, we assessed these laudable climate action targets from the financial development and sustainable energy perspectives within the E7 and G7 economies. In lieu of this, the application of Augmented Mean Group (AMG) and Quantile regression techniques on annual frequency data from both blocs between 1990 and 2019 provide useful insights into the cruciality of financial development and renewable energy in CO2 mitigation toward attaining the 1.5°C vis-à-vis the net-zero emission goals. The empirical outcome shows that renewables create paths to emissions reduction targets in both blocs. Furthermore, financial development corroborates renewables’ emission reduction roles specifically in the E7. Additionally, renewables’ interactive roles with the expanding economic growth trajectory of both blocs also induce emission-mitigating effects. Finally, an inverted U-Shaped EKC phenomenon was validated. Hence, green growth policies corroborated by financial expansion strategies are recommended and deemed apt for attaining net-zero emission targets in these strategic economic blocs.
Keywords: 1.5°C & net-zero emission; E7 & G7 economies; Financial development; sustainable environment; renewable energy; fi=Taloustiede|en=Economics|